IL-21/23 axis modulates inflammatory cytokines and RANKL expression in RA CD4+ T cells via p-Akt1 signaling - Bhattacharya, Gargee; Sengupta, Soumya; Jha, Rohila; Shaw, Shubham K.; Jogdand, Gajendra M.; Barik, Prakash K.; Padhan, Prasanta; Parida, Jyoti R.; Devadas, Satish (Frontiers in Immunology, 2023)
Introduction CD4+ T cells are critically involved in the pathogenesis of Rheumatoid Arthritis; an autoimmune disorder characterized by joint inflammation and bone degeneration. In this study, we focused on the critical role of cytokines, IL-21 and IL-23 in facilitating the aberrant status of RA Th17-like cells and report their significant contribution(s) in modulating the expression of inflammatory cytokines and RANKL. Methods Blood and synovial fluid collected from a total of 167 RA patients and 25 healthy volunteers were assessed for various inflammatory markers and RANKL expression in plasma and CD4+ T cells. Subsequent ex vivo studies examined the role of specific cytokines, IL-21 and IL-23 in mediating inflammation and RANKL upregulation by blocking their expression with neutralizing antibodies in RA CD4+ T cells and terminally differentiated human Th17 cells. Further, the role of p-Akt1 as a signalling target downstream of IL-21 and IL-23 was evinced with IL-21 and IL-23 inhibition and phospho Akt-1/2 kinase inhibitor. Results Our observations highlighted the augmented inflammatory cytokine levels in plasma and an aberrant CD4+ T cell phenotype expressing exaggerated inflammatory cytokines and membrane RANKL expression in RA as opposed to healthy controls. Neutralization of either IL-21 or IL-23 (p19 and p40) or both, resulted in downregulation of the cytokines, TNF-α, IFN-γ and IL-17 and RANKL expression in these cells, signifying the critical role of IL-21/23 axis in modulating inflammation and RANKL. Subsequent dissection of the signaling pathway found p-Akt1 as the key phosphoprotein downstream of both IL-21 and IL-23, capable of increasing inflammatory cytokines and RANKL production. Discussion Our findings unequivocally identify IL-21/23 axis in RA CD4+ T cells as a key regulator dictating two critical processes i.e. exaggerated inflammation and higher RANKL expression and provide critical targets in their downstream signalling for therapeutic approaches.